GAMBARAN KASUS KEGAWATDARURATAN PASIEN SERANGAN HEWAN DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT SAIFUL ANWAR MALANG TAHUN 2012-2016, 2021, DAN 2022 - Anom Josafat; Munsifah Zaiyanah; Taufiq Abdullah (Faculty of Medicine Universitas Mataram, 2022)
Background Indonesia as a tropical country with thousands of islands is one of the most diverse populations of animals in the world. Some of them are harmful towards humans. The research aim is to know and review the incidents of animal attacks that were reported to Saiful Anwar Hospital, Malang. The Method using a descriptive research method. Sample taken between 2012-2016, 2021, and 2022. The total of the sample is 362, all of which are patients that came to the ER of Saiful Anwar Hospital, Malang with complaints of animal attacks. The Results In the gender variable, there are 253 men and 109 women.. In the complaints variable, pain is the most frequent complaint, with 178 cases reported, followed by swelling 122 cases, 120 wound cases, 12 dizzy cases, 11 nauseous cases, 6 itchiness cases, 3 general weakness cases, and 2 diarrhea cases. In age variables, 260 patients were 18-60 years old, followed by 70 patients aged <18 years old, 32 patients >60 years old. The triage variables results are 120 patients sorted as green, 239 as yellow, and 3 as red. The cause of the attacst are 268 snake cases, followed by 36 unidentified cases, 24 dog cases, 17 scorpion and feline caused, and 3 monkey cases. Conclusion: The incident of animals attack tend to decrease every year, mostly man was the victim with age of 18-60 years old. The most frequent animal that cause the bite was snake, and P2 was the most cases in the ED